Frequency of theta rhythm is controlled by acceleration, but not speed, in running rats - Kropff, Emilio (2021)
The theta rhythm organizes neural activity across hippocampus and entorhinal cortex. A role for theta oscillations in spatial navigation is supported by half a century of research reporting that theta frequency encodes running speed linearly so that displacement can be estimated through theta frequency integration. We show that this relationship is an artifact caused by the fact that the speed of freely moving animals could not be systematically disentangled from acceleration. Using an experimental procedure that clamps running speed at pre-set values, we find that the theta frequency of local field potentials and spike activity is linearly related to positive acceleration, but not negative acceleration or speed. The modulation by positive-only acceleration makes rhythmic activity at theta frequency unfit as a code to compute displacement or any other kinematic variable. Temporally precise variations in theta frequency may instead serve as a mechanism for speeding up entorhinal-hippocampal computations during accelerated movement.